Gingivitis Associated With STD On Underage Patient Without Parental Consent - Luh Putu Eka Sriwijayanti; I Wayan Gede Artawan Eka Putra; R.A. Tuty Kuswardhani; I Made Dharma Atmaja (Jurnal Health Sains, 2023)
A 16-year-old male patient came to a private dental practice presenting chief complaints about frequent gum bleeding when brushing his teeth. The patient came without his parents. Anamnesis and clinical examination result shows that the patient was suspected of having gingivitis associated with sexually transmitted disease. No medical treatment was performed on the patient because the patient was not accompanied by parents while the patient was not legally able to sign informed consent. The patient was educated about sexually transmitted diseases and asked to come back after taking blood and urine tests, with his parents to accompany him during the examination because the patient. The patient then came back with the results of the blood and urine tests, but without his parents. The dentist cannot provide dental treatment because underage patients must be accompanied by their parents in performing a non-emergency medical treatment. Dentists have the right to postpone the non-emergency medical procedures in private practices for these patients. Dentists are obliged to provide education and refer patients to the hospital for further examination and treatment in accordance with government programs and applicable legal provisions in Indonesia.